Relative Hypodense Vertebral Artery Sign on Computerized Tomography in Atherosclerotic Near Occlusion - Muhammad Faraz Raghib; Slaven Pikija (Case Reports in Neurological Medicine)
A 52-year-old white male presented with an acute onset of slurred speech along with hypoesthesia in the entire left arm. The acute computed tomography (CT) showed relative hypodensity in the intracranial segment of left vertebral artery (VA) that was not present in historical images, pointing to the possible lack of flow. The site of occlusion was confirmed by magnetic resonance imaging (MRI) that showed susceptibility effect in the affected artery. By means of historical native CT comparison the site of VA thrombosis was correctly predicted. Local atherosclerotic thrombosis of the VA could be relatively hypodense on native CT and still have positive susceptibility weighted imaging (SWI) sign.